Pembinaan Teknik Bercocok Tanam Hidroponik Tanaman Obat di Perumahan Josroyo - Ika Purwidyaningrum; Iswandi Iswandi; Meta Kartika Untari (Journal of Dedicators Community, 2020)
The development of the Hydroponic Planting Technique for Medicinal Planting in the Central Java Josroyo Housing was carried out with the aim of improving the quality of health and the economy of the community. Pollution is a daily consumption for residents living in big cities and densely populated settlements. On free roads, motor vehicle fumes mixed with cigarette smoke are almost inevitable. Health research about cigarette smoke that causes lung cancer is not new and widely reported by researchers. Hydroponics is a method of planting that is positive for health. Consuming vegetables and medicinal plants hydroponics is better than conventional vegetables and free of pesticides so it is healthy. Vegetables and medicinal hydroponic drugs are fresher and tastier than similar products from the market or vegetable vendors. The durability of vegetables and hydroponic medicinal plants is recognized relatively longer than vegetables grown above ground. The advantages of hydroponic planting methods are saving land, saving water, without pesticides, free of weed disturbances, on-target nutrition as well as saving land and labor so as to answer the problem of planting in Josroyo housing